2018
DOI: 10.1088/1361-6382/aac6a5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical systems analysis of the cubic galileon beyond the exponential potential and the cosmological analogue of the vDVZ discontinuity

Abstract: In this paper we generalize the dynamical systems analysis of the cubic galileon model previously investigated in [1] by including self-interaction potentials beyond the exponential one. It will be shown that, consistently with the results of [1], the cubic self-interaction of the galileon vacuum appreciably modifies the late-time cosmic dynamics by the existence of a phantom-like attractor (among other super-accelerated solutions that do not modify in any appreciable way the late-time dynamics and hence are n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 101 publications
1
27
0
Order By: Relevance
“…Here we summarize the result of Ref. 573. The solutions that arise only in the vacuum case, but that are not found when background matter is considered, are the following:…”
Section: A Covariantmentioning
confidence: 81%
See 3 more Smart Citations
“…Here we summarize the result of Ref. 573. The solutions that arise only in the vacuum case, but that are not found when background matter is considered, are the following:…”
Section: A Covariantmentioning
confidence: 81%
“…482 for the exponential potential, and then in Ref. 573 for potentials beyond the exponential one. It was shown that a kind of vDVZ discontinuity arises: It is not possible to recover all of the vacuum solutions of the theory by going to the continuous limit when the matter density vanishes.…”
Section: Cosmological Analogue Of the Vainshtein Screeningmentioning
confidence: 98%
See 2 more Smart Citations
“…where the constant σ is the self-coupling parameter, we get the cubic galileon action in the Einstein's frame (EF) [83,84]:…”
Section: Horndeski Theories Of Gravitymentioning
confidence: 99%